Orange Scrub With Lemongrass (ORRIN) - Dona Martilova; Nila Windria Pebri; Niken Ayu Kurniawati; Deya Aliyah Maysaroh; Endang Sri Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2024)
Women are known for their focus on beauty, especially skin care. Outdoor activities expose the skin to sunlight, dust and pollution, causing skin problems. Using traditional body care in the form of scrubs made from natural ingredients such as orange peel and lemongrass can clean the skin deeply. Making natural body scrubs from orange peel and lemongrass is done because there is still an abundance of orange peel waste along with increasing public awareness of skin health and beauty. This product aims to utilize natural ingredients for skin care. The method for this community service activity is divided into 3 stages, namely the survey stage, the production stage and the marketing stage. The results obtained from this activity are the Orange Scrub With Lemongrass product which has been marketed to various groups of society. Marketing carried out both directly and indirectly has had a very good impact on this product.